2020
DOI: 10.1210/clinem/dgaa757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment of Periodontitis on Incretin Axis in Obese and Nonobese Individuals: A Cohort Study

Abstract: Context Periodontitis confers an increased risk of developing type 2 diabetes and, in patients with obesity, it might interfere with the incretin axis. The effect of periodontal treatment on glucoregulatory hormones remains unknown. Objective To evaluate the effect of periodontal treatment on incretin axis in obese and lean non-diabetic individuals. Setting K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Those differences were detected in the final percent of PD > 4 mm, percent of PD > 5 mm, and percent of full-mouth bleeding (Table 1 ). Another study by Suvan et al [ 15 ••] demonstrated at 6 months that, although a significant reduction in mean PD and percent of BOP is detected in comparison with baseline, those parameters were significantly higher in obese compared to non-obese with similar mean CAL and percent of BOP in the baseline (Table 1 ).…”
Section: Impact Of Obesity On Periodontal Treatmentmentioning
confidence: 95%
See 4 more Smart Citations
“…Those differences were detected in the final percent of PD > 4 mm, percent of PD > 5 mm, and percent of full-mouth bleeding (Table 1 ). Another study by Suvan et al [ 15 ••] demonstrated at 6 months that, although a significant reduction in mean PD and percent of BOP is detected in comparison with baseline, those parameters were significantly higher in obese compared to non-obese with similar mean CAL and percent of BOP in the baseline (Table 1 ).…”
Section: Impact Of Obesity On Periodontal Treatmentmentioning
confidence: 95%
“…Periodontitis is not only associated with periodontal tissue breakdown but also associated with systemic diseases, such as cardiovascular disease and other metabolic diseases [ 3 , 4 ]. Additionally, individuals with obesity have been identified as having worse periodontal conditions in different populations [ 11 , 12 •, 13 , 14 , 15 ••]. Women may present greater prevalence of periodontitis and poorer periodontal parameters compared to non-obese women [ 14 , 15 ••].…”
Section: Obesity and Periodontitis Associationmentioning
confidence: 99%
See 3 more Smart Citations